Cultural Values in Malay Pantun of Jambi: Preserving the Identity and Cultural Heritage of the Jambi Community - Nazurty Nazurty; Putimasurai Putimasurai; Urip Sulistiyo; Desti Angraini (STAI Hubbulwathan Duri, 2025)
Pantun is a traditional form of Malay oral literature widely used in rituals and social events, functioning as a medium for expressing cultural values. In Jambi, Indonesia, pantun is integral to the community’s cultural and linguistic identity. This study aims to explore the cultural values embedded in the Malay pantun of Jambi and examine its role in preserving local heritage.This research employed a qualitative descriptive design using a content analysis approach. A corpus of pantun was collected through oral traditions, archival materials, and interviews with cultural practitioners in Jambi. The analysis focused on interpreting the meaning, cultural symbolism, and values conveyed through the pantun.The analysis revealed that Jambi’s Malay pantun reflects the community’s worldview and social norms, functioning as a vehicle for transmitting cultural identity. The pantun emphasizes values such as respect, harmony, and wisdom, and demonstrates the community’s linguistic richness. It also plays a significant role in maintaining and promoting the Jambi Malay language.The findings highlight the pantun's function not only as literary expression but also as a cultural archive that strengthens communal identity and intergenerational continuity. Revitalizing the pantun tradition is essential for preserving the cultural heritage and language of the Jambi Malay community.